NOTE ON POLAR COORDINATES - LISKA, Vladimir (Trends in education, 2010)
This article deal with a appropriate use of polar coordinates. We show by an example that routine transformation of Cartesian coordinates to polar coordinates in a two-dimensional integral can lead to lengthy calculation. Appropriate use of polar coordinates on the same example will substantially simplify the calculations.
Keywords: two-dimensional integral; Fubini's theorem; polar coordinates.